Collecting the Past
1 online resource (154 pages)
Keywords: Today’s libraries and museums are heavily indebted to the passions and obsessions of numerous individual collectors who devoted their lives to amassing collections of books, manuscripts, artworks, and other culturally significant objects. Collecting the Past brings together the latest research on a wide range of significant British collectors from the eighteenth to the twentieth centuries, including Hans Sloane, Sarah Sophia Banks, Thomas Phillipps, Sydney Cockerell, J. P. Morgan Jr., Alfred Chester Beatty and R. E. Hart. Contributors to the volume examine the phenomenon of collecting in a variety of settings and across a range of different materials. Considering the aims and motives that led these collectors to assemble such remarkable collections, the book also examines the history of these collections after the collector’s death. Particular attention is given to the often complicated relationship between collectors and the public institutions that subsequently came to house their collections. Situated within the framework of cultural collecting more generally, this book offers an authoritative series of essays on key collectors. Collecting the Past should be most interesting to researchers, academics and postgraduate students engaged in the study of museum studies, book history, manuscript studies, museum history, library history and the history of collecting. Professionals in libraries, museums and galleries will also find the volume of great interest.